Flashcards for Vocabulary Development in Students with Intellectual Disabilities: EFL Teachers’ Perceptions - Pratiwi, Anggun Siska; Fithriani, Rahmah (LPPM Universitas Advent Indonesia, 2026)
Vocabulary building is a central challenge in English as a Foreign Language classrooms, especially for students with intellectual disabilities who often experience cognitive and emotional barriers in learning new words. Visual instructional media such as flashcards are frequently used to support vocabulary learning, yet their effectiveness depends on how teachers perceive and apply them in inclusive classrooms. This study aims to explore an EFL teacher’s perception of the usefulness of flashcards in supporting vocabulary building for students with intellectual disabilities. The study employed a qualitative descriptive case study design involving one EFL teacher in an inclusive junior high school in Indonesia. Data were collected through classroom observations, semi structured interviews, and lesson plan analysis, and analyzed using thematic analysis. The findings reveal that flashcards are perceived as useful for reducing cognitive load, fostering psychological safety, and enabling adaptive instructional tempo without lowering learning expectations. In conclusion, the study suggests that the usefulness of flashcards lies in teachers’ pedagogical reasoning and adaptive use rather than in the media itself, highlighting the importance of teacher cognition in inclusive EFL instruction.